PEMBUATAN LEMBAR KERJA SISWA BERBASIS ICT DENGAN MENGINTEGRASIKAN MSTBK MATERI GETARAN, ENERGI, DAN MOMENTUM UNTUK MENCAPAI KOMPETENSI SISWA SMA KELAS XI - Dilla Oktantia (Universitas Negeri Padang, 2014)
Integration of other knowledge that relevant to physics is important to reach of national learning outcome. Today, worksheet that integrated MSTDC is not available. To solve the problem is make worksheets that integrating MSTDC on web especially in Information, Communication, and Technology (ICT). Purpose of this research were to determine validity, practicality, and effectively of worksheet. Instruments that are used for validation sheet, practicality sheet, pretest and posttest sheets, and observation sheet the character of students. Data are analyzed by describing, graphs, descriptive, and correlated. The result of this research consists of two results. First, worksheet has high validity with value according to lecturers and teachers, respectively 81.05 and 78.05. Second, the value of the practicality worksheets by students is 83.42 and correlated analysis is used to found the effectively of worksheet and worksheet effective to improving learning outcomes with correlated value is -22.18 and improving character of students with correlated value is -17.39